Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

Violences conjugales : du combat féministe à la cause publique - Delage, Pauline (Domaine Genre, 2017)
« Si la violence conjugale est aujourd'hui reconnue comme une question de société légitime, il n'en a pas toujours été ainsi. C'est grâce aux mobilisations féministes des années 1970, qui définissent alors la violence dans le couple comme une violence faite aux femmes - produit des rapports de domination entre les hommes et les femmes -, que ce phénomène est sorti de la dénégation sociale dans laquelle il était tenu. Comment une cause féministe devient-elle un problème public dont s'emparent les associations, les institutions internationales et l'État ? À travers la question des violences conjugales et en comparant des cas français et américain, à Paris et à Los Angeles, Pauline Delage analyse avec acuité quelles sont, de part et d'autre de l'Atlantique, les formes légitimes de l'intervention publique dans le domaine de l'intime et des inégalités sexuées. » -- Résumé de l'éditeur.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; cycles supérieurs; europe; fem7000; france; histoire et politique; mobilisation; périodes historiques; rapports de domination; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; transféminisme; violences; violences conjugales; états-unis

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Médiation familiale : quelle place pour les violences conjugales ? - Casas Vila, Glòria (Empan, 2009)
Cet article vise à rendre compte des enjeux sexués sous-jacents à la mise en place de la coparentalité en France, notamment à partir du développement du dispositif de la médiation familiale, en relation avec la problématique des violences masculines dans le cadre de la famille. En effet, un ensemble de dispositifs légaux récemment promulgués redéfinissent les rapports entre les parents (notamment les pères) et les enfants après une séparation ou un divorce. Au-delà des rapports de filiation, ces réformes juridiques pèsent également sur les rapports entre ex-conjoints : des rapports traversés par les inégalités de genre et marqués, dans certains cas, par l’emprise et la violence que les hommes exercent sur les femmes.
Keywords: cours; cycles supérieurs; discipline; droit; europe; fem7000; france; médiation; régions géographiques; science politique et droit; thématiques; violences; violences conjugales

Les coulisses de l'État social : enquête sur les signalements d'enfant en danger - Serre, Delphine (Cours et travaux, 2009)
Pour expliquer le contexte et les critères de signalement par les professionnels de l'administration sociale d'affaires d'enfants maltraités, D. Serre a mené des entretiens auprès d'assistantes sociales et les a suivies dans leurs différentes activités. Cette enquête révèle ce que représente la catégories d'enfants en danger et ce que l'acte de signaler signifie pour les professionnels.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; enfance; europe; fem7000; france; inégalités; maltraitance; maternité; protection de l'enfance; régions géographiques; sciences humaines; sciences sociales; services sociaux; systèmes d'oppressions; thématiques; travail social; violences